Causes, Regularities and Consequences of the Current Institutional Crisis - Demirchyan, Movses (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The development of society cannot be imagined without contradictions and crises, which are particularly acute in today’s information society, where values and norms governing people’s lives are being freely interpreted and reevaluated. At the same time, new meanings are not generally binding, leading to reconstruction of the whole system of social relations, and instead of going through a crisis of social institutions – family, education, morality, etc., the role of socialization take the teams and groups. Simultaneously, the destruction of regulating social and cultural life – nation, state, truth, morality, etc., leads to their secularization in the personal and public consciousness. Man, this way acts in social relationships not as a creator, but only as a consumer dictated by social institutions minimal meanings and values, downmixed to .